Treatment of Coal Mine Acid Water Using Nf270 Membrane as Environmentally Friendly Technology (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2020)
Ex-mining pond water is widely used for the daily needs of the people these days, such as bathing, washing, and even drinking. Over time, it turns out that coal mine acid water has polluted the environment. The use of membrane technology to produce water that meets drinking water quality standards by the Minister of Health Regulation No. 492 of 2010 can be a solution to this problem. The NF270 membrane is a membrane process between reverse osmosis and ultrafiltration, which has a lower flux and operating pressure below 0.2-1.53 Mpa compared to reverse osmosis. Membrane NF270 is used for the reclamation of wastewater, water purification and softening, seawater desalination, and others. Its high rejection of organic molecules with a molecular weight of 200-2000 Da ions and multivalent can remove suspended solids, natural organic matter, bacteria, viruses, salts, and divalent ions contained in water, including coal mine acid water. The purpose of treating acid mine drainage with the NF270 membrane is to remove COD, TSS, TDS, and Fe metals. The NF270 membrane was used in this study to treat the coal mine acid water of PT. Bukit Asam. The performance of the NF270 process was assessed from the effect of pressure (4, 5, and 6 bar) on the flux and rejection rate of each parameter in a single solution, mixed and aqueous coal mine acid solution. The optimum pressure of the NF270 membrane for all parameters was 6 bar. This optimum pressure was then used to compare the phenomenon of flux that occurred and the level of rejection produced in the original sample of coal mine acid water. In the original coal mine acid water, there was a significant decrease in flux due to fouling deposition on the membrane surface. This phenomenon of decreasing flux was caused by fouling and polarization concentration. The rejection rates produced for the parameters of COD, TSS, TDS, and Fe with NF270 membranes were 56.4-93.1%; 78.5-100%; 43-69.3%; 67-100% respectively. Treated coal mine acid water using NF270 membrane technology can be used as drinking water that meets the standards of the Indonesian Ministry of Health Regulation. Thus, NF270 membrane technology can be used to process coal mine acid water into environmentally friendly drinking water.